K-12 Teachers' Perceptions and Experiences in Starting to Teach Computer Science - Astrid K. Northrup; Andrea C. Burrows Borowczak; Timothy F. Slater (MDPI AG, 2022)
New curriculum reform across the United States requires teacher educators to rapidly develop and implement professional development (PD) for K-12 teachers, newly assigned to teach computer science (CS). One of the many inherent challenges in providing valuable PD is knowing what it is that novice CS teachers most need. This quantitative research study was designed to inform the iterative development of a K-12 CS Teaching Endorsement program offered at a small college in the rural Rocky Mountain west, based on participants' perceptions of the program, before and after attempting to teach the CS curriculum provided by the endorsement program. The overarching research question guiding this study is: What differences might exist between teachers' perceived needs for CS-based professional development before and after actual classroom teaching experiences with CS? To pursue this question, the following null hypothesis was tested: H0: No measurable change exists in teachers' perceptions regarding the impact of PD before and after teaching. The research study used a 29-item Likert-style survey, organized into categories to measure participants' perceptions across five subscales. Thirteen teachers completed the targeted K-12 CS Endorsement program in May and July 2021, seven of whom subsequently taught CS in K-12 schools for the first time. Of these seven, 100% participated in this research study. After gaining classroom experience, the survey results showed very few differences before and after the endorsement program. These results suggest that CS-based PD can be more effective if the PD better targets enhancing teachers' confidence in teaching actual students and providing more useful classroom-ready instructional materials rather than targeting improving teachers' knowledge of CS concepts.